Using Microsoft Publisher 97 - Willett, Edward, 1959- (Que, 1997)
Design professional publications; create documents for the WWW; learn the most efficient way to create stunning tables and graphs; use multiple fonts to enhance your publications; add graphics and special design effects; build letterheads, brochures, banners, posters, and more; use Word's clip art in your publication; and add color and shadows to elements of your publication.